PENGUATAN TATA KELOLA KEUANGAN MELALUI PENDAMPINGAN AUDIT SEDERHANA BAGI UMKM - Maharani, Destin Alfianika; Hasibuan, Reza Rahmadi; Supriatin, Dyah (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
This community service activity aims to strengthen financial governance through simple audit assistance for Micro, Small, and Medium Enterprises (MSMEs) under the Muslimah Enterprener community. The activity addresses common issues such as poor financial record-keeping, lack of structured financial statements, and limited understanding of simple audit practices. The method used consists of three stages: preparation, implementation, and evaluation. The implementation includes socialization, interactive discussions, and practical training in preparing simple financial reports and applying audit checklists. The results indicate a significant improvement in participants’ knowledge and skills in financial management, particularly in preparing income statements and cash flow reports. Participants also showed increased awareness of the importance of transparency and accountability in managing business finances. This program proves that participatory and practical approaches are effective in improving MSMEs’ financial governance. It is recommended to conduct continuous assistance and integrate digital financial tools to ensure sustainability and broader impact.